(untitled) (Research, Society and Development, 2023)
The whitefly Bemisia tabaci is a global pest, well-known for its capacity to transmit begomoviruses during sap sucking (<24h). Chemical control is mainly adopted, aiming to kill the insect before it acquires and transmits virus. In the present study, we evaluated the toxicity of 17 insecticides on B. tabaci and subsequently determined the lethal time for this pest (only for the insecticides that caused B. tabaci mortality equal to or greater than 80%). Here, we present an efficient methodology for assessing the toxicity in the individual adult. We also provided an investigation regarding the residual effect of insecticides to control B. tabaci on cabbage in greenhouses. The selectivity of these insecticides for the predator minute pirate bug Orius tristicolor was also assessed. Bifenthrin, cartap, chlorfenapyr and chlorpyrifos caused ≥ 80% mortality on whitefly adults. They also showed fast lethal effect (<24 h), principally cartap, which caused 100% of mortality in only 45 min. However, these insecticides showed a short residual period of whitefly control (<3 days) and did not present physiological selectivity for O. tristicolor. In terms of whitefly management, only a few insecticides were efficient to avoid begomoviruse transmission. The short residual period and the absence of physiological selectivity for the predator suggests that the use of these products should involve a sustainable approach. Taking pest population levels into account when making control decisions and for predator preservation in the agroecosystems should positively contribute to more sustainable whitefly management.